2020
DOI: 10.1002/cjce.23785
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on foam formation through deformable porous media

Abstract: Foam formation in porous media is a topic of growing scientific and industrial interest due to its range of applications, from daily life consumer products to oil recovery. Despite the work done so far on foams flowing through complex structures, such as rigid porous media, this subject still needs to be fully elucidated. An additional complexity to the problem arises when the porous medium is deformable, a situation which has only been faced, to our knowledge, from a modelling point of view. In this work, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The latter investigation (Schrefler and Scotta, 2001) has led to these investigations using a simpler solution so that the behavior of surfactant alone can be understood. Graziano et al (2020) used deformable substrates to form foam; they showed that bubble size decreases as a function of number of squeezes until a plateau value is reached. A similar behavior for the mass of foam produced was found earlier by Johnson et al (2020a), where it was found that after five compression/decompression cycles no further foam would be produced (Johnson et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The latter investigation (Schrefler and Scotta, 2001) has led to these investigations using a simpler solution so that the behavior of surfactant alone can be understood. Graziano et al (2020) used deformable substrates to form foam; they showed that bubble size decreases as a function of number of squeezes until a plateau value is reached. A similar behavior for the mass of foam produced was found earlier by Johnson et al (2020a), where it was found that after five compression/decompression cycles no further foam would be produced (Johnson et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the paper fields encompass advanced modelling, [1,2] green fuel production (CO 2 hydrogenation [3] and methanation, [4] CH 4 reforming [5] ), advanced drug production, [6] biochemical food production (microalgae [7] and yeast [8] based), biomedical engineering, [9] process plant management, [10] effluent remediation (for waste water [11] and waste gas [12] streams), polymeric materials, [13] and chemical engineering fundamentals. [14] As it can be seen, all the papers are deeply rooted in chemical engineering science and technology. The wide range of fields and topics covered, as well as the variety of human needs addressed, are what basically makes chemical engineering, the evergreen discipline to which we have all committed our lives, so challenging and thus so exciting.…”
mentioning
confidence: 99%